The comparison of the therapeutic effect of Mefenamic acid and Mefenamic acid plus vitamin E on severity of pain in primary dysmenorrhea - M Yaghmaei; M Mir teimoori; M Mokhtari; M Mohammadi (JRI, 2005)
Introduction: Dysmenorrhea is one of the most gynecologic problems. Primary dysmenorrhea defines as painful menstruation in the absence of pelvic disease. Prostaglandin released from the endometrium at the time of menstruation causes primary dysmenorrhea. The Frequent treatment in pain relief for primary dismenomhea are taking non steroidal anti inflammatory drugs (NSAIDs) and oral contraceptives. In order to achieve an appropriate pain relief in primary dysmenorrhea in patients who do not have a good response to NSAIDs, this study was designed to compare the therapeutic effect of Mefenamic acid plus placebo with Mefenamic acid plus vitamin E. Materials and Methods: In this double blind clinical trial 64 single girls who were below 30 years old and suffered from primary dysmenorrhea were randomly divided in two groups. In one group Mefenamic acid plus vitamin E and in the other group Mefenamic acid plus placebo were given for their two subsequent menstruations. Results: The results confirm that the mean pain intensity before and after treatment in the group who received Mefenamic Acid and Vit E was (48.53±17.52) and in the group who received Mefenamic Acid and placebo was (25.94±21). Pain relief in the group who received Mefenamic acid and vitamin E was better than the group who received Mefenamic acid and placebo (p<0.001). Conclusion: In patients with primary dysmenorrhea who do not achieve appropriate pain relief with Mefenamic acid, we suggest to intake Mefenamic acid plus vitamin E instead.
Keywords: Primary dysmenorrhea, Pain, Dysmenorrhea, Mefenamic acid, Vitamin E, Prostaglandin